(untitled) (Academia Science Repository, 2023)
In recent decades, national and cultural characteristics of behavior have become the subject of research in many areas of the humanities. Gratitude is one of the main communicative categories that regulate behavior. In this paper, the speech act of gratitude is considered as a category of politeness of speech etiquette in intercultural communication on the basis of Russian, Uzbek and English languages.